Análisis de sucesión vegetal tras dos años del incendio forestal originado en el Cerro Putzalahua. - Muso Jami, Bryan Stalin (2023)
The main objective of this project is to analyze the vegetation succession after the forest fire that occurred in the Putzalahua Hill in 2020. For this, the area affected by the fire was determined and two sampling points were chosen to make direct observations of the plant species present in the area. The direct observation point sampling method was used because it is the most appropriate for field data collection and allows for the collection of qualitative information on the affected species. Subsequently, an inventory of the plant species present in the area was carried out and a total of 36 species were catalogued. To evaluate the recovery of the area after the fire, the current plant species inventory was compared with that of 2019 using the Jaccard index, obtaining a coincidence of 0.1851. This indicates that the area is still in the process of recovery and that plant succession is still ongoing. On the other hand, it was identified that the plant families with the greatest recovery and partial dominance in the area were the Asteraceae family and the Poaceae family. This can be attributed to the fact that these families have characteristics that allow them to resist extreme conditions, such as those that occur after a forest fire. In conclusion, the results obtained in this project allow us to understand the dynamics of plant succession after a forest fire and provide valuable information for the management and conservation of vegetation in the affected area.